Organic Matter and Plant Nutrient Distribution in a Chir (Pinus roxburghii) Plantation - Kaul, O. N.; Negi, J. D. S.; Sharma, D. C.; Shrivastava, P. B. L. (Indian Forester, 1981)
The distribution of dry matter and plant nutrients in various tree components for a 44 years old chir (Pinus roxburghji) plantation crop have been discussed. As a result of harvesting, nearly 62 to 87 per cent of the above-ground nutrients contained in the stand are removed.